How CSR is helping IDLC to become sustainable & how CSR activities are impacting on SME’s revenue generation - Sharmin, Antara Nishat (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2016.